Hazardous waste classification : Amendments to the European Waste Classification regulation - what do they mean and what are the consequences? - Wahlström, Margareta; Hjelmar, Ole; Oberender, Anke; Wik, Ola; Laine-Ylijoki, Jutta (Nordic Council of Ministers, 2016)
In European legislation, waste is classified either as hazardous or non-hazardous. Hazardous waste is a waste that due to its (intrinsic) chemical or other properties poses a risk to the environment and/or human health. The legislation for waste classification was revised in 2014 in order to align it with the chemical legislation, the CLP Regulation, but some criteria and assessment procedures for the interpretation of the hazardousness were left open. Waste classification has several implications on the waste management. This report presents challenges in the hazardous waste classification. In this report, the authors express their views on the interpretation of the waste status, especially focusing on the potentially recyclable high volume waste streams. Also recommendations for the assessement of some hazardous properties are included.
Available in PDF.
Click on the READ icon for view only access. Downloading is not available to non-subscribers - PDF icon is inactive.
Keywords: Hazardous substances -- Europe -- Classification.; Hazardous substances; Europe; Classification